2001
DOI: 10.1056/nejm200108093450604
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Sinovenous Thrombosis in Children

Abstract: Sinovenous thrombosis in children affects primarily neonates and results in neurologic impairment or death in approximately half the cases. The occurrence of venous infarcts or seizures portends a poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
761
13
61

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 994 publications
(881 citation statements)
references
References 28 publications
26
761
13
61
Order By: Relevance
“…45 The frequency of this complication is probably underestimated as brain CT can initially be normal and vascular MRI not always performed. 46,47 As vascular MRI allows better definition of cerebral tissues such exam has to be recommended. Thrombosis are currently under review in the FRALLE protocols.…”
Section: Discussionmentioning
confidence: 99%
“…45 The frequency of this complication is probably underestimated as brain CT can initially be normal and vascular MRI not always performed. 46,47 As vascular MRI allows better definition of cerebral tissues such exam has to be recommended. Thrombosis are currently under review in the FRALLE protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The second group consists of conditions causing blood flow disturbance. The third group comprises all causes of inflammation, infection, or damage to the sinus wall [3].The classic presentation of CST is severe illness associated with typically high and swinging fever. As the clot proliferates along the sinus, it is accompanied by peri-venous inflammation, tenderness, and jugular lymphadenopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cerebral sinovenous thrombosis (CSVT) in childhood is estimated at 0.67 per 100 000 children per year with approximately half occurring in neonates. 25,26 Major presenting clinical features of CSVT include seizures, fever and lethargy. 25,26 The most recent review of infants with CSVT found that 90% had predisposing factors identified (Table 2), with 16% of these patients having multiple risk factors.…”
Section: Venous Thrombosismentioning
confidence: 99%
“…25,26 Major presenting clinical features of CSVT include seizures, fever and lethargy. 25,26 The most recent review of infants with CSVT found that 90% had predisposing factors identified (Table 2), with 16% of these patients having multiple risk factors. 26 The superior and lateral sinuses are the most frequently involved vessels.…”
Section: Venous Thrombosismentioning
confidence: 99%